The organizational and economic mechanism of attraction of digital technologies in the innovation activity of companies in the conditions of international competition - Zybareva, Oksana V.; Shylepnytskyi, Pavlo; Ozarko, Kateryna; Kravchuk, Iryna; Нагорнюк, Оксана (My University, 2023)
The article is dedicated to the analysis of the organizational and economic mechanism of the participation of digital technologies in the innovative activities of companies in conditions of international competition. The theoretical and methodological basis of the study are the provisions of economic theory, the theory of innovations, the digital economy; as well as the special methods of analysis and synthesis, induction and deduction, scientific generalization, which allowed to obtain a conceptual holism of the investigation. It has been studied that the concept of organizational and economic mechanism must be understood as a system of really functional organizational, economic and legal instruments, which in a complex way determine the result of the companies' activities, and which includes the regulation of the internal economic mechanism, the general operating mechanism of companies and their innovative componentwith the participation of digital technologies
Keywords: Organizational-economic mechanism, digital technologies, digital transformation, digital economy, digitalization, international competition, innovative activity, enterprises.